Mobile-Based E-Sociometry Application Development at the Counseling Guidance Laboratories of the State Islamic Institute (IAIN) Bukittinggi (Knowbase : International Journal of Knowledge in Database, 2021)
Sociometry is something that can be used in studying the structure of social relations among a group of individuals on the basis of research on social relations and social status of each member of the group concerned. Currently the service of sociometric instruments in the guidance and counseling laboratory of the Bukittinggi State Islamic Institute is still using conventional techniques using Ms.Excel. It is done manually using the distribution of questionnaires, Ms.Excel, which is still combined with Ms.Acces, which is not online yet , so that it can only be distributed in labor, and the next problem is that the application that uses Ms.Excel cannot yet display sociometric reports graphically. The research method that the author uses is the R&D Research & Development method with a waterfall SDLC (System Development Life Cycle) system development model consisting of the Communication.Planning.Modeling stages. Construction.Deployment. For the product test that the author did, the results obtained: the validity test by the validator obtained a value of 0.85 with valid criteria, the practicality test by the practitioner obtained a value of 0.83 with the Very Practical criteria, and the effectiveness test by the effectivator obtained a value of 0.75 with the Very Effective criteria.